The Smurfs - Kerner, Jordan; Gosnell, Raja.; Peyo.; Weiss, David Nathan; Stem, J. David; Vergara, Sofía; Azaria, Hank; 1972-; 1979-; Mays, Jayma; 1973-; Harris, Neil Patrick; et al. (Culver City, Calif., 2011)
The evil wizard Gargamel chases the tiny blue Smurfs out of their magical village and into the middle of Central Park in New York and they must find a way to return to their village before Gargamel finds them.
Keywords: Wizards; Drama; Drama; Magic; Drama; Smurfs (Fictitious characters); New York (N.Y.); Drama; Animated films; Comedy films; Drama; Video recordings for the hearing impaired; Feature films; Video recordings for people with visual disabilities; Animated films; Drama; Comedy films; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired